2011
DOI: 10.1108/14636691111174225
|View full text |Cite
|
Sign up to set email alerts
|

Social networks, legal innovations and the “new” music industry

Abstract: Purpose -Digital technological innovations are commonly perceived to be radically disrupting the power or role of corporate actors within the music industry and their established industrial practices and interests. In particular, the internet is widely regarded as having produced a ''crisis'' for the music industry. While such assumptions reflect the predominance of technological deterministic thinking in relation to the music industry, this paper aims to draw upon historical insights from past research on rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…In the current technological development and knowledge economy background, the structural evolution of the music industry will also have an impact on the relationship between the music production industry, particularly the protection of copyright and the relationship between profits [51,63,64].…”
Section: Digital Music Production Industrymentioning
confidence: 99%
“…In the current technological development and knowledge economy background, the structural evolution of the music industry will also have an impact on the relationship between the music production industry, particularly the protection of copyright and the relationship between profits [51,63,64].…”
Section: Digital Music Production Industrymentioning
confidence: 99%
“…Digital technology has continued to evolve into online audio streaming technology [26] and cloud digital locker [27] technology, which bring convenience to consumers. However, the music industry needs to adjust itself to this new technology, especially in the areas of copyright protection and business loss and profit, which will affect the sustainable development model of every enterprise in the industry chain [28,29].…”
Section: Music Production Industrymentioning
confidence: 99%
“…Based on these discussions, one can conclude that the music industry is considered as a "creative industry"; because artists and audiences can have their own creative use of new digital technology. In this regard, Preston and Rogers (2011) argued that Internet and new digital technologies have enhanced opportunities for independent artists, and this new digital environment encourage a "do-it-yourself" approach, even for audiences. On the other hand, independent artists can more easily use from the new digital media in order to advance in the path of their promotion.…”
Section: Music Industry As a Creative Industrymentioning
confidence: 99%
“…As emphasized by Kjus (2016), distribution is the center of music industry in new media context. However, along with all the benefits of digital technologies, the internet is noted as a sort of "crisis" factor for music industry in some researches (Preston and Rogers 2011), and some researchers have noted the dangers of music digital "piracy" (McCarthy 2013). Eventually, based upon the strongly explanations, Koh, Murthi, and Raghunathan showed that, in the presence of "legal" distribution channels for digital music (like Beeptunes in Iran), the negative effect of online music piracy on physical music sales has weakened and finally "digital music, not online music piracy, substitutes for physical music" (Koh et al 2014).…”
Section: Introductionmentioning
confidence: 99%